Legal-Literary Explorations: Approaches to the Representation of Law in Literature. - Azalde León, José Mario; Rivera Cáceres, Ruth Melina; Aranibar Barriga, María Alejandra; Garcia Paco, Lidia Nathalia (Ius Humani. Jornal do direito, 2024)
This article investigates the possible approaches between law and literature, exploring how legal analysis can be enriched through literary narratives. Although the boundaries between law and literature are clear, the research focuses on how literary works offer insights into freedom, justice, and law. It examines how law is represented in literature and how these representations contribute to a deeper understanding of fundamental legal concepts. The article is structured into four sections. First, it examines the insularity of law and the lack of progress in interdisciplinary studies, which affect legal education and reinforce legal positivism. The second section explores the possible relationships between law and literature, analyzing how different authors have addressed legal themes in their works. The third section addresses the interpretations and theoretical complexities of the interdisciplinary approach, promoting a dialogue between various schools of thought. Finally, the fourth section presents legal dimensions in literature, in a quest to operationalize the proposed interdisciplinary categories. The main conclusion of the article is that the integration of literature into the study of law provides a platform to explore and challenge legal conventions. This interdisciplinary approach enriches both legal science and literary studies, providing a more comprehensive and critical understanding of legal phenomena. By combining legal and literary analyses, the development of law as a dynamic and progressive discipline is advanced, better equipped to respond to contemporary challenges.